Secure Data Encryption Through a Combination of AES, RSA and HMAC - Harba, E. S. I. (Engineering, Technology & Applied Science Research, 2017)
Secure file transfer based upon well-designed file encryption and authorization systems expend considerable effort to protect passwords and other credentials from being stolen. Transferring and storing passwords in plaintext form leaves them at risk of exposure to attackers, eavesdroppers and spyware. In order to avoid such exposure, powerful encryption/authentication systems use various mechanisms to minimize the possibility that unencrypted credentials will be exposed, as well as be sure that any authentication data that does get transmitted and stored will be of minimal use to an attacker. In this paper we proposed a method to protect data transferring by three hybrid encryption techniques: symmetric AES algorithm used to encrypt files, asymmetric RSA used to encrypt AES password and HMAC to encrypt symmetric password and/or data to ensure a secure transmitting between server-client or client-client from verifying in-between client and server and make it hard to attack by common attacked methods.